Practical civil engineering - Jayasree, P. K.; Balan, K. (Engineering teacher); Rani, V. (Boca Raton : CRC Press, 2021)
"The book provides primary information about civil engineering to both a civil and non-civil engineering audience in such areas as construction management, estate management, and building. Basic civil engineering topics like surveying, building materials, construction technology and management, concrete technology, steel structures, soil mechanics and foundations, water resources, transportation and environment engineering are explained in detail. Codal provisions of US, UK and India are included to cater to a global audience. Insights into techniques like modern surveying equipment and technologies, sustainable construction materials, and modern construction materials are also explained"--
OCLC-licensed vendor bibliographic record.
Keywords: Civil engineering; TECHNOLOGY / Construction / General; TECHNOLOGY / Engineering / Civil